A Case of Verrucae Resolution by Homoeopathic Medicine: A Case Report - Chaudhary, Harshit; Krishna Ghosh, Ram; Debnath, Bhaskar; Banerjee, Aniruddha (Clinical Medicine And Health Research Journal, 2023)
Warts are one of the common dermatological disorders caused by human papilloma viruses encountered in our day to day life. These are cutaneous or mucosal infection needs proper care and treatment to prevent its transmission and complete healing. Although mostly warts are dealt with the therapeutic approach, i.e. on the basis of its peculiar type and location but it can even be successfully treated by constitutional approach. This article is regarding a case of warts treated successfully with Rhus Tox followed by Ferrum Met selected as the simillimum and proved its effectiveness in a short period of time.